2017
DOI: 10.1016/j.foreco.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Forest dynamics and disturbance regimes in the Italian Apennines

Abstract: 11Forests of the Apennines are characterised by high canopy cover and high tree species diversity (being at 12 the interface between two major climatic zones of Europe), and provide important ecosystem functions 13 to millions of people. They exemplify cutting-edge themes such as forest ecology in warmer climates, 14 consequences of heavy land use, and resilience at the trailing edge of the distribution of many European 15 forest species (Silver fir, Norway spruce, Beech, Black pine, Birch). 16We introduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 106 publications
4
44
0
1
Order By: Relevance
“…This could be due to the fact that forests of these regions are mainly distributed along Apennines, a geophysical homogeneous structure that connects both northern and southern regions of the Italian peninsula, as well as the Adriatic and the Tyrrhenian sides. Our probabilistic sample of the Italian forests is consistent with a highly connected system where the virtual absence of dispersal barriers and the presence of a comparable past history (Vacchiano, Garbarino, Lingua, & Motta, ) determined a strong compositional overlap among the forest plant communities of these two biogeographical regions. Therefore, Apennines could represent a biogeographical transition zone (Morrone, ).…”
Section: Discussionsupporting
confidence: 73%
“…This could be due to the fact that forests of these regions are mainly distributed along Apennines, a geophysical homogeneous structure that connects both northern and southern regions of the Italian peninsula, as well as the Adriatic and the Tyrrhenian sides. Our probabilistic sample of the Italian forests is consistent with a highly connected system where the virtual absence of dispersal barriers and the presence of a comparable past history (Vacchiano, Garbarino, Lingua, & Motta, ) determined a strong compositional overlap among the forest plant communities of these two biogeographical regions. Therefore, Apennines could represent a biogeographical transition zone (Morrone, ).…”
Section: Discussionsupporting
confidence: 73%
“…Mediterranean forests show fundamentally different structural characteristics from temperate mesic forests, due to the high-drought stress Mediterranean forests experience during the summer and due to fire disturbance (Karavani et al, 2018). The role of wildfires in shaping the structure of Mediterranean primary forests is particularly complex as today most wildfires are humaninduced (Ganteaume et al, 2013;Vacchiano, Garbarino, Lingua, & Motta, 2017). These conditions may hinder the development of structural features typically associated with old-growth stages, such as deadwood or large trees (Burrascano et al, 2013;Kulakowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Apennine climate is a mountain variant of the Mediterranean type, with mean temperature ranging from 0 to 11°C in Jan and from 24 to 28°C in Jul; total annual precipitation varies between 600 and 4,500 mm, with frequent snowfall events above 1,000 m a.s.l. (Vacchiano et al, 2017). The montane zone (800-2,000 m a.s.l.)…”
Section: Study Areamentioning
confidence: 99%
“…Numerous studies on European treelines have concluded that recent tree establishment above upper treeline results primarily from reduced human pressure (Gehrig-Fasel, Guisan, & Zimmermann, 2007;Motta, Morales, & Nola, 2006;Treml, Senfeldr, Chuman, Ponocna, & Demkova, 2016) because of a progressive decline in the profitability of mountain agriculture (Gotsch et al, 2004;Leuch, 2005). In the Apennines, land abandonment occurred later and was related to property shifts and urbanization processes in the lowland, favouring the natural secondary succession (Bracchetti, Carotenuto, & Catorci, 2012;Caballero et al, 2009;Pelorosso, Leone, & Boccia, 2009;Torta, 2004;Vacchiano, Garbarino, Lingua, & Motta, 2017). Shifting agricultural economies have caused an increasing exodus from mountain and rural areas in general (Chauchard, Carcaillet, & Guibal, 2007;Didier, 2001;Motta & Garbarino, 2003), causing widespread spontaneous reforestation (Conti & Fagarazzi, 2005;Gellrich, Baur, Koch, & Zimmermann, 2007;MacDonald et al, 2000).…”
Section: Introductionmentioning
confidence: 99%